Rapid detection of feline parvovirus using RAA-CRISPR/Cas12a-based lateral flow strip and fluorescence - Chen, Han; Zhang, Hailing; Guo, Jie; Meng, Xiangshu; Yao, Mengfan; He, Longbin; Nie, Xiaoxuan; Xu, Han; Liu, Chao; Sun, Jian; Wang, Fei; Sun, Yuelong; et al. (Frontiers in Microbiology, 2025)
Feline parvovirus (FPV) causes severe gastroenteritis and leukopenia in cats, with high morbidity and mortality, necessitating a rapid and effective antigen diagnostic test with high sensitivity and specificity. In this study, a diagnostic platform based on a combination of Recombinase-Aided Amplification (RAA) and CRISPR/Cas12a was established for detecting FPV. Cas12a recombinant protein was purified using Nickel-Nitriloacetic Acid resin after heterologous expression in Escherichia coli. The results of RAA-CRISPR/Cas12a can be detected with a fluorescence reader or lateral flow strips (LFS) for on-site detection. The RAA-CRISPR/Cas12a-LFS had a detection limit of 2.1 × 100 copies of recombinant plasmids per reaction, compared with 2.1 × 103 copies for conventional PCR analysis. Furthermore, no cross-reactivity was observed for the RAA-CRISPR/Cas12a assay with feline coronavirus, feline herpesvirus, and feline calicivirus, demonstrating reasonable specificity. Additionally, 43 cat fecal samples with suspected clinical signs were assayed with RAA-CRISPR/Cas12a-LFS and conventional PCR in parallel. The RAA-CRISPR/Cas12a-LFS showed a 100% coincident rate with PCR. In summary, a novel, visual, sensitive, and specific detection assay based on RAA and CRISPR/Cas12a was developed for FPV.